2020
DOI: 10.1186/s41927-020-00164-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the short-term mortality of patients with rheumatoid arthritis admitted to intensive care units

Abstract: Background Patients with rheumatoid arthritis (RA) have high mortality risk and are frequently treated in intensive care units (ICUs). Methods This was a retrospective observational study. This study included 67 patients (20 males, 47 females) with RA who were admitted at the ICU of our institution for ≥48 h between January 2008 and December 2017. We analyzed the 30-day mortality of these patients and the investigated prognostic factors in RA patients admitted to our ICU. Results Upon admission, the median a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(96 reference statements)
0
3
0
1
Order By: Relevance
“…Varias publicaciones mencionan a las infecciones como causa principal de admisión a terapia intensiva 10,11,12 , en nuestro trabajo sin embargo las causas médicas que motivaron la internación a UCI fueron en primer lugar la insuficiencia respiratoria aguda, seguida del estado de shock, causas también mencionadas en este orden por el trabajo de Dumas et al 9 , y solo un 11% de nuestros pacientes presentaron infecciones documentadas como motivo de ingreso.…”
Section: Resultsunclassified
“…Varias publicaciones mencionan a las infecciones como causa principal de admisión a terapia intensiva 10,11,12 , en nuestro trabajo sin embargo las causas médicas que motivaron la internación a UCI fueron en primer lugar la insuficiencia respiratoria aguda, seguida del estado de shock, causas también mencionadas en este orden por el trabajo de Dumas et al 9 , y solo un 11% de nuestros pacientes presentaron infecciones documentadas como motivo de ingreso.…”
Section: Resultsunclassified
“…Furthermore, a French cohort study involving patients with SRDS demonstrated that infection and SRD exacerbation were the most common causes of ICU admission [ 20 ]. Godeau and Wang et al also reported that infection was the most frequent cause of ICU admission and mortality [ 21 , 22 ]. Barrett et al in 2017 reported higher rates of severe sepsis and poorer prognosis in SRD patients than in the general population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have shown that the use of corticosteroids for the treatment of SRDs leads to a poorer prognosis as a result of short-term hospitalization in the ICU [ 22 , 27 ]. Patients with SRDs often have multiple comorbid conditions such as pulmonary dysfunction, renal dysfunction, and hypertension that can affect the prognosis of ICU admission [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As several reports have shown, disease activity in uences treatment effectiveness and patient satisfaction, while treatment cost is an independent factor of treatment satisfaction (10,12,13,38) 39), but continuous use of higher doses should be avoided due to risk of infection, osteoporosis, diabetes mellitus, thrombotic stroke, cardiovascular diseases, and death (40)(41)(42)(43). However, discontinuation of prednisolone has been achieved in only nearly half of 508 patients with early RA in recent study (39); the inability to taper prednisolone has been reported as one of the characteristics of di cult-to-treat RA (44).…”
Section: Discussionmentioning
confidence: 99%